Design of Portable Air Conditioner Cooling Combination System Using Thermo Electric Cooler and Water Cooler Based on Arduino Uno - Wiharti, Wiwik; Abadi, Akbar; Mayura, Yona; Indriana, Falia; Ngoc, Nguyen Thi Bich (International Journal of Advanced Science Computing and Engineering, 2023)
A room can be categorised as comfortable or not depending on the temperature and humidity of the air in the room. In order for the room temperature to be maintained, an Air Conditioner (AC) is needed. In the AC there is refrigerant as the most important component that functions to provide cool and cold effects in the room. However, refrigerant leakage in AC is one of the causes of greenhouse emissions that have an impact on climate change. In order to reduce the emissions caused by AC usage, many researchers are utilising Peltier as a device designed to replace the AC cooling system. In order for TEC to work optimally when cooling the air in the room, it is necessary to design a combination system of Portable Air Conditioner (AC) cooling using TEC and Arduino Uno-based water cooler. The working principle of designing a portable Air Conditioner cooling combination system using TEC and water cooler requires a temperature set point value in the water cooler system, where the Arduino is given a set point temperature range on the heatsink. The temperature on the heatsink affects the pump speed. if the higher the temperature on the heatsink read by the DS18B20 temperature sensor, the pump will work quickly to cool the heatsink side. The temperature on the heatsink, pump speed, and the height of the water cooler in the tub are displayed on the LCD. Before assembling and arranging the components that will be used in the portable Air Conditioner cooling combination system using TEC and water cooler, the design flow of the working principle and tool design of the portable Air Conditioner cooling combination system is needed. After the components are assembled and arranged, the test results are obtained with the conclusion that the TEC with the water cooler method is better at cooling a room measuring 1x1 metre than the water cooler method.